Effectiveness of platelet rich plasma versus corticosteroid in the treatment of plantar fasciitis: a double-blind randomized controlled trial - Das, Shukha Ranjan; Rashid, Muhammad Mamun Ur; Sardar, Kawsar; Hassan, Mehdi; karmakar, Chandra Shekhar; Bhuiyan, Md Abu Rasel; Jewel, ABM Sarwar Jahan (Journal of the Bangladesh Society of Anaesthesiologists, 2022)
Background: Plantar fasciitis is a common cause of heel pain. This condition is caused bydegenerative changes resulting in repetitive microtears of the plantar fascia, which are in turn causedby biomechanical overuse from prolonged standing or running. Several nonoperative treatments havebeen employed, such as stretching, physical therapy, nonsteroidal anti-inflammatory drugs,extracorporeal shock wave therapy, needling and night splints, relative rest, etc. But clinical outcomesof these methods are controversial. Corticosteroid is also effective but provides only short-term painrelief with disappointing long-term results. This procedure is also associated with complications,including localized infection, fat pad atrophy, and plantar fascia rupture. In recent years, platelet-richplasma (PRP) has been investigated as a treatment option for plantar fasciitis. PRP is a bioactiveconcentrate of various growth factors and cytokines that modulate cell proliferation and differentiation,angiogenesis, and chemotaxis. Objectives: To evaluate the effectiveness of platelet rich plasma versus corticosteroid in the treatmentof plantar fasciitis. Materials & method: This Quasi-experimental study was carried out on adult patients with chronicPlantar Fasciitis attended in Dhaka Medical College Hospital, during the period of October 2021 toMay 2022. The patients were randomly assigned to one of the two groups; group A (patients treated withPRP); group B (patients treated by with corticosteroid). After providing the allocated treatment, allpatients were undergone follow-up examination at 1st week, 1st month, 3rd month and at 6th month forclinical improvement. Visual Analog Scale (VAS), Roles and Maudsley (RM), and Foot Function Index(FFI) scoring systems were used as outcome measures. Result: Mean ± SD of age was calculated to be, 42.31 ± 7.6 for Group A and 42.29 ± 8.0 for Group B.Most of the participants in Group A [13 (72.1)] & in Group B [15 (65.2)] were females. Mean VAS scoreat different follow up time reveals, after 1 week of intervention, score was turn down or pain reduced inboth groups, but comparatively better in group B. At 3rd month (Mean VAS 3.05 & 4.82 in group A &B respectively) and 6th month later (Mean VAS 1.67 & 4.12 in group A & B respectively) follow upperiod, significant improvement was found in group A. Use of corticosteroid (Group B) showedimprovement in symptoms immediately at 1st week to one month (short duration), which did not lastlong. But PRP effective in prolong time. RM score shows that a significant difference among two groupsat 1 and 3 months with P = 0.051 and P = 0.001, respectively. Mean FFI scores in Group A weresignificantly lower than Group B. No adverse events were noticed in any of the groups. Conclusion: Platelet-rich plasma (PRP) injection is better than steroid injection in relieving the painof planar fasciitis and improvement function of the patient foot. JBSA 2022; 35 (2) : 22-29